A Critical Review of Presentation, Practice and Production Task-based Language and Lexical Approaches - Nouriya Muftah E. Elsaadi (Abhat Journal, 2018)
Although the Presentation, Practice and Production (PPP henceforth) has been criticised by a number of academics such as Lewis, (1996) and Willis (1996), it is still prevalent in second language acquisition and very popular in several situations, since it is easy to master and an effective technique for managing large classes. Therefore, several attempts have been made both by researchers and language instructors to find and use of the most efficient teaching practices aimed at enhancing language production and affecting learning outcomes in a positive way. Therefore, this article aims to examine the critical opinions about (PPP). Two proposed alternatives are discussed in terms of support in accordance with their broad usage, application and constraints; then the conclusion to the discussion is stated. The paper suggests that if learners’ needs and expectations are known and considered in the pre-planning stages of lessons, any language teaching model may be favourable for teachers.